r = 1 ∑ n r 3 ( r n ) = 2 n − 3 ( n 3 + a n 2 + b n + c )
Find the value of a 2 + b 2 + c 2 if the above equation is true for all integers r and n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Best and the quickest solution is to put value of (r,n) as (1,1), (1,2) and (1,3) (as the given equation is valid for all r and n) and obtain 3 simple equations in a, b and c.
For (r,n)= (1,1): The equation is -> a+b+c=3
For (r,n)= (1,2): The equation is -> 4a+2b+c=12
For (r,n)= (1,3): The equation is -> 9a+3b+c=27
Solving the above equations, we get a=3, b=0 and c=0
Hence, a^ 2 +b^ 2 +c^ 2 = 9
This is wrong. You did not prove that it's true for all values of n .
Can you generalize that summation please
Simulated for n = 10, 11, 12, 13 and 14:
I actually found b = n - 1 and c = n when a = 2, OR b = 2 (n - 1) and c = 2 n when a = 1.
I applied a = 2, b = n - 1 and c = n for
n 3 + 2 n 2 + ( n − 1 ) n + n = n 3 + 2 n 2 + n 2 − n + n = n 3 + 3 n 2 + 0 + 0 .
Not a genuine way but a 2 + b 2 + c 2 = 3 2 + 0 2 + 0 2 = 9 is determined.
Answer: 9
Problem Loading...
Note Loading...
Set Loading...
We start by writing r 3 ( r n ) as a linear combination of binomial coefficients . Note that
r 3 = r ( r − 1 ) ( r − 2 ) + 3 r ( r − 1 ) + r
The summation becomes
= r = 1 ∑ n [ r ( r − 1 ) ( r − 2 ) + 3 r ( r − 1 ) + r ] ( r n ) r = 4 ∑ n [ r ( r − 1 ) ( r − 2 ) ( r n ) ] + 3 r = 3 ∑ n [ r ( r − 1 ) ( r n ) ] + r = 2 ∑ n [ ( r ( r n ) ]
Note that
r ( r − 1 ) ( r − 2 ) ( r n ) = = = = r ( r − 1 ) ( r − 2 ) ⋅ ( n − r ) ! r ! n ! ( n − r ) ! ( r − 3 ) ! n ! n ( n − 1 ) ( n − 2 ) ⋅ ( n − r ) ! ( r − 3 ) ! ( n − 3 ) ! n ( n − 1 ) ( n − 2 ) ⋅ ( r − 3 n − 3 )
Similarly, r ( r − 1 ) ( r n ) = n ( n − 1 ) ⋅ ( r − 2 n − 2 ) and r ( r n ) = n ( r − 1 n − 1 ) .
Our sum is equal to
n ( n − 1 ) ( n − 2 ) r = 3 ∑ n ( r − 3 n − 3 ) + 3 n ( n − 1 ) r = 2 ∑ n ( r − 2 n − 2 ) + n r = 1 ∑ n ( r − 1 n − 1 ) .
Once we apply the property j = 0 ∑ n ( j n ) = 2 j , the summation simplifies to
n ( n − 1 ) ( n − 2 ) ⋅ 2 n − 3 + 3 n ( n − 1 ) ⋅ 2 n − 2 + n ⋅ 2 n − 1 = 2 n − 3 ( n 3 + 3 n 2 ) .